Comparison between Carotid Intima-Media Thickness and Coronary Artery Calcification in the Prediction of Atherosclerosis in Diabetic Patients - Rusli Muljadi; Bachtiar Murtala; Peter Kabo; FX Budhianto Suhadi (The Prodia Education and Research Institute (PERI), 2014)
BACKGROUND: Cardiovascular disease is one of the atherosclerosis etiologies that can lead to death. Diabetes mellitus increases the risk of atherosclerosis. Screening tool is very beneficial for detecting atherosclerotic plaque, especially in subclinical atherosclerotic cases. Carotid intima-media thickness (CIMT) and coronary artery calcification score (CACS) are two kinds of tools that are widely used, and each of these tools has its own superiority. This study was aimed to investigate the sensitivity and specificity of both of these tools as screening tools.METHODS: The study was conducted with a cross sectional design involving 43 diabetic and 68 non-diabetic male subjects aged above 45 years old. All subjects fulfilled inclusion criteria. Carotid artery ultrasonography and CACS measurement were performed.RESULTS: Fischer exact test was used to show a significant correlation between CIMT and CACS (p<0.05). Diagnostic test was used to assess the sensitivity of CIMT toward CACS in above 75 percentile. The left common carotid artery (LCCA) showed the highest sensitivity either in diabetic (76.4%) or non-diabetic male subjects (90%).CONCLUSION: CIMT has the same sensitivity with CACS. CIMT can be used as the preferred screening tool for high risk patients and as a substitution tool to CACS for low risk patients in subclinical atherosclerosis detection.KEYWORDS: atherosclerosis, diabetes mellitus, carotid intima-media thickness, coronary artery calciication score